Heat-pipe based thermal management designs for Lithium-ion batteries - Lei, Shurong (2019)
Lithium-ion (Li-ion) battery, as a promising future main power source, has attracted tremendous attention by a surge of growing interest in electric vehicles (EVs). Performance of this energy conversion device highly depends on its operating thermal conditions. This thesis focuses on thermal issues in applications of Li-ion battery in varying thermal environments from a low to a high ambient temperature, and developments of effective and innovative battery thermal management (BTM) systems. Particular interests are paid to BTM designs based on heat pipes, for which both theoretical investigations and experimental tests were performed to achieve desirable thermal improvements for Li-ion operation. From the theoretical and numerical perspective, the major challenge for heat pipe is to effectively capture the coupling two-phase flow, mass and heat transfer in porous media. To this end, this thesis formulates three sets of governing equations to describe these multiphase transport phenomena at the representative-elementary-volume (REV) scale using the Darcy’s law and its Darcy-Forchheimer and Darcy-Brinkman modified equations. In so doing, the theoretical models can effectively describe liquid-vapor two-phase flows under the impacts integrating the Darcy forces, capillary force, inertial forces and viscous forces. Importantly, a couple of multi-distribution-function lattice Boltzmann (LB) algorithms are developed to solve these equations, by which detailed numerical studies of not only single-phase flow or heat transfer in porous media but also water-vapor flow with phase change in a flat heat pipe were obtained. These theoretical demonstrations and numerical findings clearly reveal distinct flow and heat transfer characteristics of two-phase fluids in heat pipes; the proposed LB models are demonstrated as viable and powerful numerical tools for studying these complex transport phenomena. With the aids of these theoretical and numerical progress, this thesis further extends to the corresponding BTM experiments to develop a new and efficient thermal management means to dissipate battery heat in a swift manner when it locates in an adverse thermal environment. A BTM cooling design based on heat pipe and water-spray was invented and its effectiveness for LiFePO4 batteries discharging at an ambient temperature 40ºC as validated by a series of experiments. It turns out that the proposed heat-pipe based spray-cooling BTM design in this thesis achieved a fast heat dissipation for Li-ion battery. It effectively restrains a rapid rise of battery temperature—the maximum temperature-rise-rate of battery with the proposed BTM is only 13.5% or 28.0% of that without BTM or with BTM based on heat pipe with forced air convection. The design facilitates for a large variety of applications of Li-ion battery a simple but highly efficient BTM means to ensure its normal operation even at a large discharging current and an unfavorable thermal environment. The innovations of BTM in this thesis also include another smart design which integrates thermal storage using phase change material (PCM) and spray-cooling based on heat pipe. Experiments were conducted to assess this interesting design and it is confirmed to be applicable not only as a heating source for Li-ion battery idled in a cold environment, but also as swift and flexible cooling means for battery working at moderate and high ambient temperatures. This has been evidenced by the comparison to battery without BTM that the proposed BTM extends the period of battery temperature dropped to 0ºC by 4.5 times in cold environment, and decreases the battery average temperature by 45.4% and 28.5% in a moderate and high ambient temperatures. These dual BTM functions greatly extend the application scope of BTM for Li-ion battery, and also improve the energy-utilization efficiency of the corresponding power system.